Comparing Minor Connector Castability of Printed Cast Partial Dentures to Conventional Cast Partial Dentures: An In-vitro Study - Meghna Budati; Suresh Venugopalan (Journal of Clinical and Diagnostic Research)
Introduction: Partial denture prostheses are used to restore missing teeth and oral function, with minor connectors playing a crucial role in the denture framework. Traditionally, Cast Partial Dentures (CPD) are made using wax patterns and metal casting; however, this process can sometimes result in issues such as porosity or distortion. Advances in digital dentistry have introduced 3D printing, which offers a new method for creating denture frameworks with greater precision. However, the impact of 3D printing on the castability of minor connectors compared to conventional methods remains underexplored. Aim: To compare the minor connector castability of manually CPDs to Direct Metal Laser Sintering (DMLS) printed partial dentures. Key objectives include assessing the minor connector castability between the two groups, manual and DMLS, before and after wax-up and casting. Materials and Methods: This in-vitro study was conducted in the Department of Prosthodontics at Saveetha Dental College, Chennai, Tamil Nadu, India from July 2023 to December 2023. A total of 10 samples were included and divided into two groups. Group 1 consisted of five samples of manually CPDs, while group 2 included five samples of DMLS printed partial dentures. A standardised casting procedure was followed for both the manually cast and DMLS printed partial dentures to evaluate their minor connector castability. The two groups were compared for wax-up and casting. To assess castability, the number of lattice framework holes in each connector was counted after wax-up and fabrication. Statistical analysis was performed using a statistical software program Statistical Package for Social Sciences (SPSS) version 23.0. The Wilcoxon signed-rank test, a non parametric test, was used, with statistical significance set at p<0.05. Results: Comparisons between the groups revealed a statistically significant difference in the medians of manual wax-up (p=0.25) and casting compared to DMLS (p=0.317) design and printing. The DMLS group demonstrated superior accuracy compared to manual casting. Conclusion: The present study demonstrates that the Removable Partial Denture (RPD) frameworks designed and produced by DMLS exhibit better castability compared to manual wax-up and casting.